2022
DOI: 10.3389/fmicb.2022.870204
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Biological Characterization of the First Mymonavirus Identified in Fusarium oxysporum

Abstract: We characterized a negative sense single-stranded RNA mycovirus, Fusarium oxysporum mymonavirus 1 (FoMyV1), isolated from the phytopathogenic fungus Fusarium oxysporum. The genome of FoMyV1 is 10,114 nt, including five open reading frames (ORFs1–5) that are non-overlapping and linearly arranged. The largest, ORF5, encodes a large polypeptide L containing a conserved regions corresponding to Mononegavirales RNA-dependent RNA polymerase and mRNA-capping enzyme region V; the putative functions of the remaining fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Multiple alignments based on the RdRp of SlMyV1 and other selected mymonaviruses were conducted ( Figure S10 ). Four conserved motifs that were identified in other mymonaviruses were also detected in the RdRp of SlMyV1 ( Hao et al., 2018 ; Wang et al., 2022 ). In addition, phylogenetic analysis revealed that SlMyV1 clustered with members of the genus Sclerotimonavirus ( Figure 8 ), suggesting SlMyV1 should be a new member of this genus.…”
Section: Resultsmentioning
confidence: 90%
“…Multiple alignments based on the RdRp of SlMyV1 and other selected mymonaviruses were conducted ( Figure S10 ). Four conserved motifs that were identified in other mymonaviruses were also detected in the RdRp of SlMyV1 ( Hao et al., 2018 ; Wang et al., 2022 ). In addition, phylogenetic analysis revealed that SlMyV1 clustered with members of the genus Sclerotimonavirus ( Figure 8 ), suggesting SlMyV1 should be a new member of this genus.…”
Section: Resultsmentioning
confidence: 90%
“…dianthi mitovirus 1 (family Mitoviridae ), Fusarium oxysporum f. sp. dianthi hypovirus 2 (family Hypoviridae ), Fusarium oxysporum ourmia-like virus 1 (family Botourmiaviridae ), Hadaka Virus 1 (family Polymycoviridae ), and Fusarium oxysporum mymonavirus 1 (family Mymonaviridae ; Sharzei et al, 2007 ; Lemus-Minor et al, 2015 ; Sato et al, 2020 ; Torres-Trenas et al, 2020 ; Torres-Trenas and Pérez-Artés, 2020 ; Zhao et al, 2020 ; Wang et al, 2021 ; Wen et al, 2021 ; Wang J. et al, 2022 ). Of these reported mycoviruses, Fusarium oxysporum f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Of these reported mycoviruses, Fusarium oxysporum f. sp. dianthi virus 1 (FodV1), Fusarium oxysporum ourmia-like virus 1 (FoOuLV1) and FoMyV1 are capable of causing hypovirulence of host and can be used as biological control agents ( Lemus-Minor et al, 2019 ; Zhao et al, 2020 ; Wang J. et al, 2022 ). This study is the first report of seven partitiviruses from F. oxysporum .…”
Section: Discussionmentioning
confidence: 99%
“…emend. Snyder and Hansen) sampled in Luòhé (漯河市), Hénán Province (河南省), China [19]; • Hubramonavirus golovinomycesae for Golovinomyces cichoracearum GcM3_contig_4635, here renamed Golovinomyces cichoracearum negative-stranded RNA virus 1 (GcNSRV1), discovered by HTS in an ascomycete (erysiphaceaen Erysiphe cichoracearum [DC.] (1805)) sampled in Shady Grove, Maryland, USA [20]; and • Hubramonavirus vitis for grapevine-associated mononega-like virus 3 (GaMLV3) discovered by HTS in common grape vine (vitaceaen Vitis vinifera L.) sampled in the Veneto region of Italy [21].…”
Section: Family Mymonaviridaementioning
confidence: 99%